2018
DOI: 10.1021/acschemneuro.8b00441
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylated Single-Walled Carbon Nanotubes Inhibit Aβ42 Fibrillogenesis, Disaggregate Mature Fibrils, and Protect against Aβ42-Induced Cytotoxicity

Abstract: The fibrillogenesis of amyloid-β protein (Aβ) is considered a crucial factor in the pathogenesis of Alzheimer’s disease (AD). Hence, inhibiting Aβ fibrillogenesis is regarded as the primary therapeutic strategy for the prevention and treatment of AD. However, the development of effective inhibitors against Aβ fibrillogenesis has faced significant challenges. Previous studies have shown that pristine single-walled carbon nanotubes (SWNTs) can inhibit fibrillogenesis of some amyloid proteins. However, the poor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 78 publications
2
63
0
Order By: Relevance
“…Aβ 40 (25 µm) was incubated with CPDs (1, 10, and 100 µg mL nanosheet could disassemble the preformed Aβ-Cu 2+ aggregates in 4 h, and graphene oxide/graphitic carbon nitride (GO/g-C 3 N 4 ) could photodegrade the aggregates of Aβ (33)(34)(35)(36)(37)(38)(39)(40)(41)(42) under UV after 100 min incubation. [63,64] Hydroxylated single-walled carbon nanotubes (SWCN-OH) significantly remodeled the Aβ 42 fibrils into small granular aggregates with the treatment for 5 h. [65] Photoactivated branched polyethylenimine-coated carbon nanodots (bPEI@CDs) distinctively facilitated the dissolution and disruption of β-sheet-rich Aβ fibrils to soluble species in 2 d. [66] Compared with the above literature data, CPDs significantly disintegrated the long and dense β-sheet rich Aβ fibrils to amorphous aggregates in 10 min, showing a high potency in the disassembly of preformed Aβ fibrils in a time scale of seconds to minutes (Figure 3c). We speculate that electrostatic interactions, H-bonding and hydrophobic interactions by the positively charged free amino groups and the skeleton of conjugated aromatic structures composed of pyrimidine rings, pyrrole rings, and benzene rings are the keys to the rapid remodeling potency of CPDs.…”
Section: Disaggregation Of Aβ 40 Fibrilsmentioning
confidence: 99%
“…Aβ 40 (25 µm) was incubated with CPDs (1, 10, and 100 µg mL nanosheet could disassemble the preformed Aβ-Cu 2+ aggregates in 4 h, and graphene oxide/graphitic carbon nitride (GO/g-C 3 N 4 ) could photodegrade the aggregates of Aβ (33)(34)(35)(36)(37)(38)(39)(40)(41)(42) under UV after 100 min incubation. [63,64] Hydroxylated single-walled carbon nanotubes (SWCN-OH) significantly remodeled the Aβ 42 fibrils into small granular aggregates with the treatment for 5 h. [65] Photoactivated branched polyethylenimine-coated carbon nanodots (bPEI@CDs) distinctively facilitated the dissolution and disruption of β-sheet-rich Aβ fibrils to soluble species in 2 d. [66] Compared with the above literature data, CPDs significantly disintegrated the long and dense β-sheet rich Aβ fibrils to amorphous aggregates in 10 min, showing a high potency in the disassembly of preformed Aβ fibrils in a time scale of seconds to minutes (Figure 3c). We speculate that electrostatic interactions, H-bonding and hydrophobic interactions by the positively charged free amino groups and the skeleton of conjugated aromatic structures composed of pyrimidine rings, pyrrole rings, and benzene rings are the keys to the rapid remodeling potency of CPDs.…”
Section: Disaggregation Of Aβ 40 Fibrilsmentioning
confidence: 99%
“…Similarly, surface‐hydroxylated single‐walled carbon nanotubes (SWNTs) can inhibit Aβ42 fibrillogenesis and disaggregate mature fibrils in a dose‐dependent manner. The interaction occurs via both hydrophobic and electrostatic forces [74] . Molecular‐dynamics simulations on SWNTs‐Aβ(16–22) interactions in water concluded that hydrophobic and mostly, π‐stacking interactions with Phe residues prevent β‐sheet formation and destabilize prefibrillar β‐sheets [75] …”
Section: Nanochaperones To Treat Misfolding Diseasesmentioning
confidence: 99%
“…The interaction occurs via both hydrophobic and electrostatic forces. [74] Molecular-dynamics simulations on SWNTs-Ab (16)(17)(18)(19)(20)(21)(22) interactions in water concluded that hydrophobic and mostly, p-stacking interactions with Phe residues prevent b-sheet formation and destabilize prefibrillar b-sheets. [75] Low surface energy is gained by proteins adsorbed on hydrophilic surfaces.T his effect is commonly exploited by covering surfaces with sterically demanding or polar polymers like polyethylene glycol (PEG).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…MWCNTs are considered potentially effective against Alzheimer's disease [10]. This is likely due to the ability of MWCNTs to inhibit Aβ42 fibrillogenesis, as well as to disaggregate mature fibrils, which protects the body from cytotoxicity induced by Aβ42 [11]. It should be noted that fullerenes and carbon nanotubes are actively used not only for the treatment of neurodegenerative diseases, but also for their diagnostics [12].…”
Section: Introductionmentioning
confidence: 99%